Analisis Natrium Siklamat pada Kue Telur Gabus yang Beredar di Pasar Ir Soekarno Sukoharjo - Ronal Tolkhah; Makhabbah Jamilatun; Dewi Saraswati Fadhillah (JURNAL ILMU KEFARMASIAN INDONESIA, 2022)
Cork egg cake is a traditional cake famous for its sweet taste. Sodium cyclamate is a sweetener that is added to snacks, one of which is cork egg cake. Excess sodium cyclamates can trigger cancer development. The Head of the National Food and Drug Agency of the Republic of Indonesia issued regulation number 4 of 2014 concerning the maximum limit for the use of food additives. The sweetener in the snack food category was 250 mg/kg. This study was conducted to determine the level of sodium cyclamate in cork egg cakes circulating in Ir. Soekarno Sukoharjo market. The type of research was quantitative with a descriptive research design. The method used in this research was qualitative analysis using the precipitation method and quantitative analysis using UV-Vis spectrophotometry. Qualitative analysis showed that samples B and C were positive for sodium cyclamate. The results of the quantitative analysis showed that the average levels of sodium cyclamate in cork egg cakes B and C were 1.02 mg/kg and 1.03 mg/kg. The concentrations of the two samples were still below the limit requirements of BPOM No. 4 in 2014.